Association between the 5′ UTR variant C178T of the serotonin receptor gene HTR3A and bipolar affective disorder - Niesler, Beate; Flohr, Thomas; Nöthen, Markus Maria; Fischer, Christine; Rietschel, Marcella; Franzek, Ernst; Albus, Margot; Propping, Peter; Rappold, Gudrun (Pharmacogenetics and genomics, 2001)
Serotonin receptor type 3 is a ligand-gated ion channel implicated in behavioural disorders. Our objective was to identify nucleotide variants in a specific portion of the 5′ region of the serotonin receptor gene (HTR3A) containing upstream open reading frames (uORFs) and to investigate their effect on bipolar disease. Mutations in uORFs have been recently shown to cause disease by changing expression on the translational level. We identified one polymorphism, C195T, and one missense mutation, C178T (Pro16Ser) within an upstream open reading frame. No significant association was found between the C195T polymorphism and bipolar affective disorder. A significant association was, however, found between the variant C178T in 156 patients with bipolar disorder compared to 156 healthy controls (P = 0.00016). To investigate the relevance of this variant on gene expression, luciferase reporter constructs containing the C178T (Pro16Ser) allele were established and compared to the C178T plus C195T and wild-type alleles. Reporter constructs containing the C178T (Pro16Ser) allele drove 245% and 138% expression compared to the wild-type allele. These findings show that the C178T(Pro16Ser) variant in HTR3A may represent a functional variant and affect the susceptibility to bipolar disorder.